Aluminum alloy surface protective coating and preparation method thereof

Through solid solution treatment, aging treatment and multi-layer conversion film technology, combined with nanoparticle deposition, a composite film layer structure is formed, which solves the problems of insufficient wear resistance and weak adhesion of aluminum alloys in the prior art, and achieves higher performance Aluminum alloy surface protective coating.

CN119433523APending Publication Date: 2025-02-14YANGZHOU POLYTECHNIC COLLEGE
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411682768.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing conversion film processes are insufficient in high friction and strong wear environments, have weak adhesion, and are prone to glass or wear, resulting in failure of protective effect.

Method used

Through solid solution treatment and aging treatment, the flatness and structural density of the aluminum alloy surface are improved, combined with the multi-layer conversion film process, and layer-deposition is used to form a composite film layer structure using silica, alumina and titanium dioxide nanoparticles.

Benefits of technology

It significantly improves the wear resistance, adhesion and corrosion resistance of the surface protective coating of aluminum alloy, extends the service life, and is suitable for higher friction environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148773380000111
    Figure BDA0005148773380000111
  • Figure BDA0005148773380000121
    Figure BDA0005148773380000121
Patent Text Reader

Abstract

The invention relates to the technical field of metal material treatment, and particularly provides an aluminum alloy surface protective coating and a preparation method thereof. The method comprises the following steps: after a to-be-treated aluminum alloy sample is cleaned and no residual liquid exists, sequentially carrying out solution treatment and aging treatment on the aluminum alloy; and immersing the obtained aluminum alloy sample into a conversion film solution, carrying out deposition treatment, and drying to obtain the aluminum alloy sample with the surface protective coating. By combining solid solution treatment and aging treatment with a conversion film process, the wear resistance of the surface of the aluminum alloy is improved, the aluminum alloy is suitable for a higher friction environment, the adhesive force and corrosion resistance of a film layer are improved through multiple treatments of solid solution, aging and the conversion film, and the service life of the aluminum alloy is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material processing, and in particular to an aluminum alloy surface protective coating and a preparation method thereof. Background Art

[0002] The conversion coating process is a commonly used aluminum alloy surface treatment method, which forms a dense protective film on the aluminum alloy surface through chemical reaction. The protective film is usually generated by the reaction of the aluminum alloy surface with the chemical substances in the conversion liquid, and the formed film layer can provide certain corrosion resistance, oxidation resistance and wear resistance. The conversion coating treatment process commonly uses phosphate, chromate or chromium-free conversion coating methods, which are widely used in aerospace, automobile, electronic equipment, construction and machinery. It is mainly used to improve the corrosion resistance and adhesion of aluminum alloys.

[0003] Although the conversion film can provide a certain degree of corrosion resistance, the hardness and wear resistance of the film are usually low. In high-friction and strong wear environments, the conversion film is prone to glass or wear, resulting in the failure of the protective effect of the film. At the same time, compared with other high-performance coatings such as anodized films or PVD coatings, the conversion film has a relatively weak adhesion problem. In some extreme environments or high-stress conditions, the film is easy to peel off.

[0004] In view of the problems of insufficient wear resistance and poor adhesion in the current conversion film process, providing a protective coating for aluminum alloy surface with better performance has become one of the technical problems that need to be solved urgently. Summary of the invention

[0005] In view of this, the present invention proposes an aluminum alloy surface protective coating and a preparation method thereof, aiming to provide an aluminum alloy surface protective coating with better wear resistance.

[0006] The technical solution of the present invention is achieved as follows: The present invention provides a method for preparing a protective coating on the surface of an aluminum alloy, comprising the following steps:

[0007] Step 1: Clean the aluminum alloy sample to be treated, ensure that there is no residual liquid on the surface, and then perform solid solution treatment and aging treatment on the aluminum alloy in sequence;

[0008] Step 2: immersing the aluminum alloy sample obtained in step 1 into a conversion coating solution for deposition treatment;

[0009] Step 3: After the deposition treatment, the aluminum alloy sample is dried to obtain an aluminum alloy sample with a surface protective coating.

[0010] In the above implementation manner, the aluminum alloy sample can use common aluminum alloy grades, such as 6061 or 2024, etc. The cleaning operation steps in step one include: cleaning the surface of the aluminum alloy with dilute sulfuric acid to remove the oxide film and surface impurities, and then rinsing with deionized water to ensure that there is no residual acid solution.

[0011] Solution treatment dissolves alloying elements in aluminum alloys, such as magnesium and silicon, into the aluminum matrix through high-temperature heating to form a uniform solid solution, which not only improves the mechanical properties of the aluminum alloy, but also removes oxides, impurities and pores on the surface of the aluminum alloy, providing a more uniform and cleaner substrate for subsequent processing.

[0012] Aging treatment can precipitate the strengthening phase in the aluminum alloy by heating, thereby increasing the strength and hardness of the aluminum alloy. The aging process can also improve the alloy's resistance to stress corrosion cracking and provide a more solid foundation for subsequent surface protective coatings.

[0013] After solution treatment and aging treatment, the surface of the aluminum alloy is smoother and more stable, and the internal stress is released, which makes the aluminum alloy surface more suitable for forming a conversion film. In addition, solution treatment and aging treatment make the surface structure of the aluminum alloy denser, reduce surface defects and microcracks of the aluminum alloy, improve the integrity and stability of the conversion film, and reduce the risk of cracking or peeling due to uneven stress.

[0014] In some embodiments, the solution treatment method includes heating the aluminum alloy sample to be treated to 500-530° C. under a protective atmosphere and maintaining the temperature for 1-2 hours.

[0015] In some embodiments, the aging treatment method includes: heating the aluminum alloy sample after the solid solution treatment to 160-190° C. under a protective atmosphere, and heat-insulating the sample for 4-6 hours.

[0016] In some embodiments, in step 2, the aluminum alloy sample is sequentially immersed in a first conversion coating solution for 3-5 minutes, immersed in a second conversion coating solution for 2-4 minutes, and immersed in a third conversion coating solution for 2-3 minutes, the first conversion coating solution contains silicon dioxide nanoparticles, the second conversion coating solution contains aluminum oxide nanoparticles, and the third conversion coating solution contains titanium dioxide nanoparticles.

[0017] In the above implementation, the aluminum alloy sample is sequentially immersed in three different conversion coating solutions, each solution contains specific nanoparticles. This step aims to improve the overall performance of the aluminum alloy surface protective film by depositing different nanoparticles layer by layer, including corrosion resistance, wear resistance, adhesion, hardness, etc. Specifically, by using three different conversion coating solutions and immersing them sequentially, a multi-layer film structure is formed, each layer of which has different functions and can complement each other to enhance the comprehensive performance of the aluminum alloy surface coating.

[0018] Silica nanoparticles have excellent corrosion resistance, wear resistance and thermal stability. Adding silica nanoparticles to the conversion film can significantly improve the chemical corrosion resistance of the aluminum alloy surface. When the aluminum alloy surface reacts with the chemical substances in the conversion solution, the silica nanoparticles are embedded in the film layer through physical adsorption and chemical bonding, forming a relatively dense film layer, which effectively prevents the erosion of corrosive substances in the external environment.

[0019] Alumina nanoparticles are a good wear-resistant and antioxidant material. Alumina particles in the conversion film can enhance the hardness and wear resistance of the film. It can further enhance the mechanical strength of the aluminum alloy surface and improve the wear resistance of the film, especially in high friction and high stress environments, where alumina particles help maintain the integrity of the film. Alumina nanoparticles are deposited in the conversion film by ion exchange and physical embedding, reacting with the oxide on the surface of the base aluminum alloy to form a dense protective layer. These particles can not only enhance the hardness of the film, but also improve the film's resistance to external mechanical damage.

[0020] Titanium dioxide nanoparticles have good UV resistance, oxidation resistance and self-cleaning properties. In the conversion film formed on the surface of aluminum alloy, titanium dioxide particles can not only improve the oxidation resistance of the film layer, but also increase the UV resistance of the film layer to a certain extent, preventing the film layer from aging or deteriorating under sunlight. In addition, titanium dioxide particles have strong hydrophilicity, which can improve the self-cleaning property of the surface to a certain extent and reduce the possibility of pollutants deposited on the surface. Titanium dioxide nanoparticles form a close bond with the conversion film through chemical deposition or physical adsorption, enhancing the weather resistance, UV resistance and self-cleaning function of the film layer. Titanium dioxide film layers usually have a higher surface energy, which helps to improve the adhesion of the film layer and can enhance the wear resistance and high temperature resistance of the film layer.

[0021] By forming a composite film layer structure, the density of the film layer is improved and its resistance to the external environment is enhanced. The nanoparticles of each layer of the film fill the microcracks and pores on the surface of the Lu alloy to varying degrees, making the film layer more uniform and smooth, and avoiding the rupture and shedding of the film layer.

[0022] In some embodiments, the first conversion coating solution includes 10-20 g / L phosphoric acid, 5-10 g / L aluminum sulfate, and 0.5-2.0 g / L silica nanoparticles.

[0023] In the above implementation mode, aluminum sulfate dissociates in a phosphoric acid environment to release aluminum ions, and these aluminum ions react with phosphoric acid on the surface of the aluminum alloy to form an aluminum-based conversion film. This film layer is usually aluminum phosphate, which has strong adhesion and corrosion resistance. During the formation of the conversion film, silicon dioxide nanoparticles are dispersed into the film layer to provide enhanced physical properties.

[0024] In some embodiments, the second conversion coating solution includes 5-10 g / L of aluminum sulfate and 0.5-3.0 g / L of aluminum oxide nanoparticles.

[0025] In the above embodiments, aluminum sulfate promotes the formation of aluminum-based conversion film on the surface of aluminum alloy by providing aluminum ions. Aluminum oxide nanoparticles fill the microstructure in the conversion film to enhance the hardness, density and corrosion resistance of the film. Aluminum oxide nanoparticles can be evenly distributed in the film layer to optimize the microstructure of the film layer, making the film layer more uniform and dense, and enhancing its wear resistance.

[0026] In some embodiments, the third conversion coating solution includes 10-15 g / L sulfuric acid, 0.5-1.5 g / L sodium titanate, and 0.5-1.0 g / L titanium dioxide nanoparticles.

[0027] In the above embodiments, titanium dioxide nanoparticles are uniformly dispersed in the conversion film solution, and as the conversion film is formed, they are deposited on the aluminum alloy surface. Due to the nanometer size of titanium dioxide, they can fill the tiny pores in the conversion film, forming a denser film layer, and enhancing the hardness and wear resistance of the film layer. The addition of titanium dioxide nanoparticles helps to form a nanocomposite structure, which can not only improve the physical properties of the film layer, but also improve the thermal stability and oxidation resistance of the film layer, so that the aluminum alloy surface can be used stably for a long time in a more harsh environment.

[0028] In some embodiments, the average particle size of the silicon dioxide nanoparticles is 20-40 nm, the average particle size of the aluminum oxide nanoparticles is 50-80 nm, and the average particle size of the titanium dioxide nanoparticles is 20-40 nm.

[0029] Due to the high hardness of silicon dioxide, it can enhance the wear resistance and scratch resistance of the film, especially in high friction environments. The particle size range of 20-40nm can increase the surface area of ​​the nanoparticles, enhance their bonding with the aluminum alloy surface, and improve the chemical stability of the film. Alumina particles with a particle size between 50-80nm are relatively large, which can form structural support in the conversion film, increase the compressive strength and overall stability of the film. The addition of aluminum oxide also helps to form a hard outer layer of the film, thereby increasing the wear resistance and surface protection ability of the film. The particle size of 20-40nm helps the titanium dioxide particles to be evenly distributed in the film, improve the hardness and durability of the film, and make the film have better UV resistance and high temperature resistance. The smaller the particle size of titanium dioxide, the greater its surface energy, and it can better combine with other nanoparticles and the surface of aluminum alloy, thereby forming a film with strong adhesion.

[0030] In some embodiments, the aluminum alloy sample is subjected to a surface plasma treatment prior to the first immersion treatment.

[0031] The performance of the conversion coating can be significantly improved by treating the aluminum alloy sample with surface plasma before the first immersion treatment. Surface plasma treatment not only helps to improve the adhesion, density and uniformity of the film layer, but also improves the corrosion resistance and wear resistance of the aluminum alloy surface itself. Especially in the process of multiple immersions in different conversion coating solutions, the aluminum alloy surface after plasma treatment can provide a more solid film layer foundation, so that the final coating has better mechanical strength, corrosion resistance and wear resistance.

[0032] In a second aspect, the present invention further provides an aluminum alloy surface protective coating, which is prepared using the above-mentioned preparation method.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] The present invention improves the wear resistance of the aluminum alloy surface by combining solution treatment and aging treatment with a conversion coating process, and is suitable for higher friction environments. The multiple treatments of solution treatment, aging treatment and conversion coating improve the adhesion and corrosion resistance of the film layer and extend the service life of the aluminum alloy. The multiple soaking and drying steps in the deposition process ensure the uniformity, density and stability of the film layer and improve the overall coating performance. The present invention provides an aluminum alloy surface protective coating that is more wear-resistant, corrosion-resistant and has strong adhesion, has significantly improved performance compared to traditional methods, and is suitable for a wider range of industrial applications. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the embodiments of the present invention belong. If the definitions set forth in this section are contrary to or otherwise inconsistent with the definitions set forth in the patents, patent applications, published patent applications, and other publications incorporated herein by reference, the definitions listed in this section take precedence over the definitions incorporated herein by reference.

[0037] Unless otherwise specified, the methods used in the following examples are all conventional methods. Unless otherwise specified, the materials, reagents and instruments used are all conventional materials, reagents and instruments in the art, and can be obtained by those skilled in the art through commercial channels.

[0038] When an amount, concentration or other value or parameter is expressed as a range, a preferred range or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including the range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range. In the present specification and claims, range definitions can be combined and / or interchanged, and if not otherwise stated, these ranges include all subranges contained therein.

[0039] In order to verify the performance of the protective coating proposed in the present application, the following examples use 6061 aluminum alloy as a test object and use different surface protection schemes for comparison, as follows.

[0040] Example 1

[0041] A 6061 aluminum alloy plate was used, washed with 10wt% dilute sulfuric acid, and then washed with deionized water until there was no residual acid on the surface. The aluminum alloy plate was then transferred to a high-temperature atmosphere furnace, heated to 520°C in a nitrogen atmosphere, kept warm for 1.5 hours, then cooled to 180°C, kept warm for 5 hours, and then cooled to room temperature.

[0042] The heat-treated aluminum alloy plate was then immersed in the first conversion coating solution for 4 minutes, then immersed in the second conversion coating solution for 3 minutes, and then immersed in the third conversion coating solution for 2.5 minutes. After the immersion was completed, it was rinsed with deionized water until there was no residual liquid on the surface. After drying, an aluminum alloy sample with a surface protective coating was obtained.

[0043] The first conversion coating solution contains 15 g / L phosphoric acid, 8 g / L aluminum sulfate, and 1 g / L silicon dioxide nanoparticles with an average particle size of 30 nm. The second conversion coating solution contains 8 g / L aluminum sulfate and 2 g / L aluminum oxide nanoparticles with an average particle size of 60 nm. The third conversion coating solution contains 12 g / L sulfuric acid, 1 g / L ammonium titanate, and 0.7 g / L titanium dioxide nanoparticles with an average particle size of 30 nm.

[0044] Example 2

[0045] This embodiment is based on Embodiment 1, except that the heat-treated aluminum alloy plate is immersed in a conversion coating solution for 9.5 minutes, wherein the conversion coating solution contains 15 g / L phosphoric acid, 8 g / L aluminum sulfate, 1 g / L silicon dioxide nanoparticles with an average particle size of 30 nm, 8 g / L aluminum sulfate, 2 g / L aluminum oxide nanoparticles with an average particle size of 60 nm, 12 g / L sulfuric acid, 1 g / L ammonium titanate, and 0.7 g / L titanium dioxide nanoparticles with an average particle size of 30 nm.

[0046] Example 3

[0047] The present embodiment is based on the embodiment 1, and the only difference is that, before the immersion treatment, it also includes treating the surface of the aluminum alloy plate with a low-temperature plasma treatment machine, the treatment gas is nitrogen, the treatment time is 5 minutes, and the treatment power is 200W.

[0048] Example 4

[0049] This embodiment is based on the embodiment 1, and the difference is only that:

[0050] The heat-treated aluminum alloy plate was immersed in the first conversion coating solution for 3 minutes, then immersed in the second conversion coating solution for 2 minutes, and then immersed in the third conversion coating solution for 2 minutes. After the immersion, it was rinsed with deionized water until there was no residual liquid on the surface. After drying, an aluminum alloy sample with a surface protective coating was obtained.

[0051] The first conversion coating solution contains 20 g / L phosphoric acid, 10 g / L aluminum sulfate, and 2 g / L silicon dioxide nanoparticles with an average particle size of 30 nm. The second conversion coating solution contains 10 g / L aluminum sulfate and 3 g / L aluminum oxide nanoparticles with an average particle size of 60 nm. The third conversion coating solution contains 15 g / L sulfuric acid, 1.5 g / L ammonium titanate, and 1 g / L titanium dioxide nanoparticles with an average particle size of 30 nm.

[0052] Example 5

[0053] This embodiment is based on the embodiment 1, and the difference is only that:

[0054] The heat-treated aluminum alloy plate was immersed in the first conversion coating solution for 5 minutes, then immersed in the second conversion coating solution for 4 minutes, and then immersed in the third conversion coating solution for 3 minutes. After the immersion, it was rinsed with deionized water until there was no residual liquid on the surface. After drying, an aluminum alloy sample with a surface protective coating was obtained.

[0055] The first conversion coating solution contains 10 g / L phosphoric acid, 5 g / L aluminum sulfate, and 0.5 g / L silicon dioxide nanoparticles with an average particle size of 30 nm. The second conversion coating solution contains 5 g / L aluminum sulfate and 0.5 g / L aluminum oxide nanoparticles with an average particle size of 60 nm. The third conversion coating solution contains 10 g / L sulfuric acid, 0.5 g / L ammonium titanate, and 0.5 g / L titanium dioxide nanoparticles with an average particle size of 30 nm.

[0056] Example 6

[0057] This embodiment is based on the embodiment 1, but the only difference is that the average particle size of the silicon dioxide nanoparticles is 20 nm.

[0058] Example 7

[0059] This embodiment is based on the embodiment 1, but the only difference is that the average particle size of the silicon dioxide nanoparticles is 40 nm.

[0060] Example 8

[0061] This embodiment is based on the embodiment 1, but the only difference is that the average particle size of the aluminum oxide nanoparticles is 50 nm.

[0062] Example 9

[0063] This embodiment is based on the embodiment 1, but the only difference is that the average particle size of the aluminum oxide nanoparticles is 80 nm.

[0064] Example 10

[0065] This embodiment is based on the embodiment 1, but the only difference is that the average particle size of the titanium dioxide nanoparticles is 20 nm.

[0066] Embodiment 11

[0067] This embodiment is based on the embodiment 1, but the only difference is that the average particle size of the titanium dioxide nanoparticles is 40 nm.

[0068] Comparative Example 1

[0069] This comparative example is based on Example 1, except that the operation of heat preservation at 180° C. for 5 hours is omitted.

[0070] Comparative Example 2

[0071] This comparative example is based on Example 1, except that the operation of heating the aluminum alloy plate to 520° C. and heat-treating it for 1.5 hours is omitted.

[0072] Comparative Example 3

[0073] This comparative example is based on Example 1, except that the operation of heating to 520° C. and heat preservation for 1.5 hours and the operation of heat preservation at 180° C. for 5 hours are omitted.

[0074] Comparative Example 4

[0075] This comparative example is based on Example 1, except that the average particle size of the silicon dioxide nanoparticles is 10 nm.

[0076] Comparative Example 5

[0077] This comparative example is based on Example 1, except that the average particle size of the silicon dioxide nanoparticles is 50 nm.

[0078] Comparative Example 6

[0079] This comparative example is based on Example 1, except that the average particle size of the aluminum oxide nanoparticles is 40 nm.

[0080] Comparative Example 7

[0081] This comparative example is based on Example 1, except that the average particle size of the aluminum oxide nanoparticles is 90 nm.

[0082] Comparative Example 8

[0083] This comparative example is based on Example 1, except that the average particle size of the titanium dioxide nanoparticles is 10 nm.

[0084] Comparative Example 9

[0085] This comparative example is based on Example 1, except that the average particle size of the titanium dioxide nanoparticles is 50 nm.

[0086] Three samples were prepared in parallel for each group of the above examples and comparative examples, and then the obtained sample aluminum alloy materials were subjected to performance tests, including hardness, salt spray test, film thickness, film uniformity, adhesion, etc. The test results are shown in the following table:

[0087]

[0088]

[0089] From the above data, we can see that:

[0090] The staged immersion method of Example 1 significantly improves the hardness, adhesion, corrosion resistance, impact resistance and thermal stability of the film layer, and performs better than Example 2. Although the immersion time of Example 2 is longer, the film layer is thin and has poor uniformity, resulting in weak overall performance.

[0091] It can be seen from the comparison between Example 1 and Example 3 that low-temperature plasma treatment has a significant effect on the improvement of film performance. Example 3 is superior to Example 1 in terms of hardness, corrosion resistance, impact resistance, adhesion and thermal stability, indicating that low-temperature plasma treatment can effectively enhance the quality and performance of the film.

[0092] The process flow and conversion coating solution ratio of Example 1 have the best effect in terms of the performance of the film layer, especially in terms of hardness, adhesion, corrosion resistance, thermal stability, etc. The different adjustments in immersion time and solution concentration of Examples 4 and 5 resulted in a decrease in the performance of the film layer, especially in terms of hardness, corrosion resistance and aging performance.

[0093] The film performance of Example 1 is the best in terms of hardness, corrosion resistance, adhesion, impact resistance, thermal stability, etc., showing the best comprehensive performance. As the particle size of the nanoparticles increases or changes, the film performance of Examples 6 to 11 gradually decreases, especially in terms of hardness, corrosion resistance and impact resistance. Due to the lack of optimized heat treatment process and process adjustment, the performance of the film of the samples of Comparative Examples 4 to 9 is generally lower than that of Example 1.

[0094] Example 1 shows the best performance in terms of hardness, corrosion resistance, adhesion, impact resistance, thermal stability, aging performance, etc., proving that the heat treatment step is crucial to improving the quality and performance of the film. The performance of Comparative Example 1 is slightly inferior. Although the 180°C insulation step is omitted, the performance is acceptable due to the retention of some heat treatment steps. The performance of Comparative Examples 2 and 3 gradually decreases, especially in terms of hardness, corrosion resistance and adhesion. The steps of heating and insulation at 520°C and insulation at 180°C for 5 hours are omitted, resulting in a serious decline in the quality of the film, and ultimately showing poor film performance.

[0095] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a protective coating on the surface of an aluminum alloy, characterized in that: The steps include: Step 1: Clean the aluminum alloy sample to be treated, ensure that there is no residual liquid on the surface, and then perform solid solution treatment and aging treatment on the aluminum alloy in sequence; Step 2: immersing the aluminum alloy sample obtained in step 1 into a conversion coating solution for deposition treatment; Step 3: After the deposition treatment, the aluminum alloy sample is dried to obtain an aluminum alloy sample with a surface protective coating.

2. The method for preparing the protective coating on the surface of aluminum alloy according to claim 1, characterized in that: The solution treatment method comprises heating the aluminum alloy sample to be treated to 500-530° C. in a protective atmosphere and heat-insulating the sample for 1-2 hours.

3. The method for preparing the protective coating on the surface of aluminum alloy according to claim 1, characterized in that: The aging treatment method comprises: heating the aluminum alloy sample after solid solution treatment to 160-190° C. in a protective atmosphere, and heat-insulating the sample for 4-6 hours.

4. The method for preparing the protective coating on the surface of aluminum alloy according to claim 1, characterized in that: In step two, the aluminum alloy sample is immersed in the first conversion coating solution for 3-5 minutes, the second conversion coating solution for 2-4 minutes, and the third conversion coating solution for 2-3 minutes. The first conversion coating solution contains silicon dioxide nanoparticles, the second conversion coating solution contains aluminum oxide nanoparticles, and the third conversion coating solution contains titanium dioxide nanoparticles.

5. The method for preparing the protective coating on the surface of aluminum alloy according to claim 4, characterized in that: The first conversion film solution includes 10-20 g / L of phosphoric acid, 5-10 g / L of aluminum sulfate, and 0.5-2.0 g / L of silicon dioxide nanoparticles.

6. The method for preparing the protective coating on the surface of aluminum alloy according to claim 4, characterized in that: The second conversion coating solution includes 5-10 g / L of aluminum sulfate and 0.5-3.0 g / L of aluminum oxide nanoparticles.

7. The method for preparing the protective coating on the surface of aluminum alloy according to claim 4, characterized in that: The third conversion film solution includes 10-15 g / L of sulfuric acid, 0.5-1.5 g / L of sodium titanate, and 0.5-1.0 g / L of titanium dioxide nanoparticles.

8. The method for preparing the protective coating on the surface of aluminum alloy according to claim 4, characterized in that: The average particle size of the silicon dioxide nanoparticles is 20-40 nm, the average particle size of the aluminum oxide nanoparticles is 50-80 nm, and the average particle size of the titanium dioxide nanoparticles is 20-40 nm.

9. The method for preparing the protective coating on the surface of aluminum alloy according to claim 4, characterized in that: The aluminum alloy samples were subjected to surface plasma treatment before the first immersion treatment.

10. A protective coating on the surface of an aluminum alloy, characterized in that: The method is prepared by any one of claims 1 to 9.

Citation Information

Cited By

  • Aluminum alloy plate with high weather resistance and self-cleaning function and preparation method thereof

    CN122128583A

  • Aluminum alloy sheet having high weather resistance self-cleaning function and method for manufacturing the same

    CN122128583B